Penggunaan Aplikasi Transportasi Online dengan Kode Promo Oleh Grab Ditinjau dari Hukum Persaingan Bisnis - Sri Wahyuni; Kiki Joesyiana; Hj. Agustin Basriani; Desi Susanti (Indonesian Journal of Business Analytics, 2022)
The modern age is currently using a lot of communication technology to make profits, especially in business, including online transportation developed by Grab. However, business actors should not engage in unhealthy business, especially the practice of setting prices lower than other competitors. Predatory pricing is a business strategy in which business actors undercut prices for a period of time with the intention of closing or disposing of competitors' businesses in the relevant market, thus creating monopolistic practices and unfair business competition, predatory pricing is regulated in Article 20 of the Law No. 5 of 1999 on the prohibition of monopolistic practices and unfair business competition. The Commission for the Surveillance of Business Competition (KPPU) has indicated to the practice of predatory pricing after the implementation of this online fare. If left unchecked, this practice is expected to harm the online transportation industry in a sustainable way. This type of research can be classified as empirical legal research, another term used is sociological because in this research, the author conducts research directly at the research site or place to get a complete and clear picture of the problem being studied. The nature of this research is descriptive qualitative with primary data sources, secondary data and tertiary data while the population and samples are online transport partners (Grab, Gojek, Maxim), consumers and KPPU. Data collection techniques are interviews, questionnaires and literature research. Two main things can be concluded from the results of the research problem. First, based on the author's research, the promo implemented by Grab is a program of Grab in the form of special short-term offers designed to attract consumers and the promo does not comply with Article 20 of the Business Competition Law and article 1365 of the Civil Code. Meanwhile, the legal consequences arising from these predatory activities are that competing companies will incur losses with the promos implemented by Grab and that the Grab company will be subject to criminal penalties in accordance with Article 48 paragraph 2 and 49 letters a, b and c if Grab has been proven to have used predatory pricing and civil penalties in the form of compensation for both material and immaterial losses to the injured parties.